"Interest Rate Trap", or Why Does the Central Bank Keep the Policy Rate Too Low for Too Long?3. (30th June 2015) - Cao, Jin; Illing, Gerhard
Abstract In this paper, we provide a framework for modeling one risk‐taking channel of monetary policy, the mechanism whereby financial intermediaries' incentives for liquidity transformation are affected by the central bank's reaction to a financial crisis. The anticipation of the central bank's reaction to liquidity stress gives banks incentives to invest in excessive liquidity transformation, triggering an "interest rate trap" – the economy will remain stuck in a long‐lasting period of suboptimal, low interest rate equilibrium. We demonstrate that interest rate policy as a financial stabilizer is dynamically inconsistent, and the constrained efficient outcome can be implemented by imposing ex ante liquidity requirements.